Gimnazija Kranj v zlatem rezu - Stritih, Tija (Igra ustvarjalnosti, 2024)
The golden ratio is the ratio we consider perfect and good-looking. It divides a line segment into two unequal parts so that the ratio of the length of the larger line segment to the smaller one is equal to the ratio of the whole length to the longer length of line segment. This ratio is approximate 1,618 and has infinitely many decimal places. The articel presents the golden ratio and its presence in nature, the human body and art. It is also found in architecture, where, because of its beauty, architects often use it in the design of buildings. In this artical is also described history of Gimnazija Kranj. In this research we wanted to find out whether the reason for the beautiful appearance of Gimnazija Kranj is actually due to the golden ratio. We therefore paid special attention to proving the presence of the golden ratio in the architectural elements of Gimnazija Kranj, using measurements from the architectural design. To help find the golden section , we have created a system of points for finding the golden ratio in the GeoGebra computer program and made a pair of compasses for the golden section. The aim or objective of this research paper is therefore to find out whether Gimnazija Kranj is built in the golden ratio. In the end, we were able to confirm its presence in Gimnazija, and we also observed golden spirals and golden rectangles on the building.
Keywords: arhitecture; arhitektura; Gimnazija Kranj; golden ratio; golden spiral; proportion; razmerje; zlata spirala; zlati rez